The effect of composition, microfluidization and process parameters on formation of oleogels for ice cream applications - E. Silva-Avellaneda (Nature Portfolio, 2021)
Abstract The use of oleogels is an innovative and economical option for the technological development of some food products, among them ice creams. The aim of this study was to establish the best processing conditions to obtain an emulsion which form oleogels with the lowest ζ-potential and average droplet size (ADS) for use as ice cream base. Using surface response methodology (SRM), the effects of three numerical factors (microfluidization pressure, oil and whey protein concentration, WP) and four categorical factors (oil type, temperature, surfactant, and type of WP) on formation of emulsions were assessed. The response variables were ζ, ADS, polydispersity index (PDI), viscosity (η), hardness, cohesiveness and springiness. Additionally, a numerical optimization was performed. Two ice creams containing milk cream and oleogel, respectively were compared under the optimization conditions. Results suggest oleogels obtained from the microfluidization of whey and high oleic palm oil are viable for the replacement of cream in the production of ice cream.